Implementasi Teknik Pengambilan Gambar oleh Director of Photography pada Pembuatan Video Feature “Menyemai Harapan, Memanen Kebersamaan” - Fatah ‘Izzani Salim; Trie Damayanti; Nurmaya Prahatmaja (BADAN PENERBIT STIEPARI PRESS, 2025)
The final project report on the production of the feature video “Menyemai Harapan, Memanen Kebersamaan” is motivated by the urgency of food security amid the urbanization of Bandung City and the need to highlight about community-based sustainable local alternative agriculture systems. This final project report highlights the role of the Director of Photography (DoP) in presenting the Community Supported Agriculture (CSA) model at Seni Tani through an engaging and informative audiovisual video. The primary objective of this report is to explain the implementation of image taking techniques, including shot types, camera angles, camera movements, and framing, as executed by the Director of Photography (DoP) during the production process. The production stages include pre-production (idea development, concept, storyboard, and shot list), production (application of image taking techniques during the shooting of local alternative farming activities at Seni Tani), and post-production (editing process and voice-over recording). The final product is a feature video that emphasizes visual storytelling to reinforce the informative and persuasive message about community-based sustainable local alternative agriculture systems at Seni Tani. The conclusion of this report indicates that the mastery of filming techniques by the Director of Photography (DoP) plays a crucial role in conveying messages visually and emotionally to the audience, thereby making this video feature an effective communication medium in raising public awareness about community-based sustainable local alternative agriculture systems.